If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(1 + 7n) = 40 + 8n (1 * 6 + 7n * 6) = 40 + 8n (6 + 42n) = 40 + 8n Solving 6 + 42n = 40 + 8n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-8n' to each side of the equation. 6 + 42n + -8n = 40 + 8n + -8n Combine like terms: 42n + -8n = 34n 6 + 34n = 40 + 8n + -8n Combine like terms: 8n + -8n = 0 6 + 34n = 40 + 0 6 + 34n = 40 Add '-6' to each side of the equation. 6 + -6 + 34n = 40 + -6 Combine like terms: 6 + -6 = 0 0 + 34n = 40 + -6 34n = 40 + -6 Combine like terms: 40 + -6 = 34 34n = 34 Divide each side by '34'. n = 1 Simplifying n = 1
| 2x^2+9x=35 | | -4x^2(5x^2-21x-y)= | | 3(x-1)=-7(x-1) | | 1-5m=6(1-m) | | 7(3x+2)+22=36 | | -0.04x+1.32=1.08 | | 4(6x+5)=2+6x | | -3(4-y)=27 | | -1(3w-4)+12w=3w+4 | | 3m-5=5m+2 | | -27-3k=-6(k+2) | | X+20=6x+5 | | 6-3(2k-4)=-18 | | -3(4-y)=-2 | | r-3.8=9.4 | | -6a+2a=-36 | | 71-17=4a+1 | | 7a-3(a+1)=6-5a | | 1.8+9=-5.7-6 | | 5(3e+5)-25e= | | t^2+9t=18 | | v+31=-3(1-6v) | | 13*4x+2x=1x*6-12 | | 9x*9x+5=41 | | -33+4k=-2(k-4)-5 | | 13*4x+2x= | | 6x^2-5x-1=3 | | -20+8r=4(-5-6r) | | X+Y=140 | | c/5-4=-3 | | 4(2n+5)+2n=36+8n | | 0=9-x^2 |